Morphological Analysis for Identification and Classification of Fungal Species Diversity in Situ Gede Area, Dramaga, Bogor - Ivan Permana Putra (Indonesian Journal of Science and Education, 2024)
Mushrooms are cosmopolitan organisms with very high biodiversity. Macro fungi, or mushrooms, are most commonly found in various regions of the tropical Earth. However, mushrooms in Indonesia have not been extensively explored and identified. Therefore, this research aims to identify several mushroom species found in the Situ Gede area, Bogor, West Java. Mushroom identification is carried out by collecting and measuring samples with a scale comparison in their natural habitat. The samples are then dried as a dry herbarium or soaked in alcohol as a wet herbarium. Four mushrooms were successfully identified, three of which belong to the phylum Basidiomycota and one belongs to the phylum Ascomycota. Some of these mushrooms include Lentinus arcularius, Lentinus sp., and Termitomyces microcarpus, which belong to the phylum Basidiomycota, while Xylaria polymorpha belongs to the phylum Ascomycota. Some fungi can be used as a source of food and also as a source of medicine.